Developing the Innovation Capabilities of SMEs : The Role of Intermediary Firms in Knowledge Ecosystems - Shahzad, Khuram; Hafeez, Shahid; Heimo, Teppo; Mäenpää, Antti; Mubarak, Muhammad Faraz; Evans, Richard (IEEE, 2025)
Knowledge ecosystems drive growth by enabling firms to access diverse, specialized, and distributed resources from ecosystem members, allowing them to address complex product innovation challenges that would be difficult to tackle independently. This approach facilitates complementary value creation. However, small- to medium-sized enterprises (SMEs) encounter significant challenges within such ecosystems due to their limited size and limited resources. This article contributes to the extant studies on knowledge ecosystems by investigating how collaborations within these ecosystems enable SMEs to both explore and exploit knowledge, enhancing their innovation capabilities. Drawing on empirical data from 33 semistructured interviews and two focus groups involving multiple stakeholders (18 SMEs, 1 large firm, and 14 intermediary firms) from a knowledge ecosystem in Ostrobothnia, Finland, this article finds that knowledge cocreation through collaboration significantly improves SMEs’ technological and collaborative capabilities, leading to growth and market expansion. Intermediary firms play a dual role, going beyond knowledge brokering by providing capacity-building support that helps SMEs better contextualize and utilize external knowledge. This article advances both theoretical and practical understanding by demonstrating how intermediary firms function not only as facilitators but also as active capacity builders in the knowledge exploitation process. This nuanced understanding contributes to the ongoing discourse on ecosystem dynamics and SME innovation. From a practical perspective, SMEs should leverage core partners and intermediaries to address their inherent resource constraints and drive innovation performance. This approach enables them to expand their networks, codevelop technological solutions, and potentially secure future funding.
Keywords: Innovative capabilities; SMEs; knowledge ecosystems; intermediary firms; knowledge exchange; small and medium-sized enterprises; fi=Aluetiede|en=Regional Studies|; fi=Markkinointi|en=Marketing|; fi=Tuotantotalous|en=Industrial Management|